Pengaruh Faktor Keuangan Mahasiswa Madiun Terhadap Keputusan Menabung Dimasa Pandemi - Agus, Muhammad (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
This study was conducted with the aim of analyzing the effect of financial knowledge, financial attitude, financial technology, financial self-efficacy, and locus of control on saving decisions. The object of this research is college students who live in Madiun city. The type of research used in this study is Quantitative Explanatory Research with non-probability sampling data collection techniques. Meanwhile, the data collection methods used were questionnaire interviews and literature study. Data was obtained by distributing questionnaires to college in students Madiun via Google Form which was then processed using the Structural Equation Model Partial Least Square (SEM-PLS). From the tests carried out, the results show that financial knowledge and locus of control have a positive and significant effect on saving decisions. Meanwhile, financial attitude, financial technology, and financial self-efficacy have no effect.